المسعى التجريبي في الرياضيات، دوره التعليمي ومساهمة الوسائط الرقمية - شطيطح, محمد; حازي, محمد; طالبي, محمد الطاهر; بوضياف, محمد (جامعة الوادي - University of Eloued, 2020)
إنّ الغاية المسطّرة لتدريس الرياضيات، في منهاج الرياضيات لمرحلة التعليم المتوسط بالجزائر، تتمثّل في امتلاك المتعلّم لأدوات التفكير والمسعى العلمي وقدرته على توظيفها في معالجة مختلف الوضعيات. جاءت دراستنا لكتاب الرياضيات المدرسي للسنة الثالثة من التعليم المتوسط حيث تركّزت على جزئه التطبيقي. تمثّلت إشكالية الدراسة في معرفة المعنى والدور التعليمي الذي أعطاه الكتاب المدرسي لمفهوم المسعى التجريبي ومدى مساهمة الوسائط الرقمية في تفعيل ذلك بما يقود إلى تحقيق الغاية التي ينشدها المنهاج من تدريس الرياضيات. اعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي وشبكة للتحليل عمدنا إلى بنائها بالارتكاز على بعض الدراسات التعليمية والوثائق التربوية الرسمية. بيّنت الدراسة أنّ مشكلات وتمارين الكتاب المدرسي المذكور لم ترق إلى طموحات المنهاج فيما يتعلّق بممارسة المسعى التجريبي، بما في ذلك إدراج الوسائط الرقمية الذي لم يكن بشكل فعّال. Abstract: The objective of teaching mathematics, in the curriculum of mathematics for intermediate education in Algeria, is that the learner has the tools of thinking and scientific approach and its ability to employ them in dealing with various situations. Within this framework, our study of the school book of mathematics for the third year of intermediate education focused on its applied part. The problem of the study was to know the meaning and educational role given by the school book to the concept of experimental approach and digital media. In this study we relied on the descriptive analytical method and a network of analysis that we built based on some educational studies and official educational documents. The study showed that the problems and exercises of the school book mentioned did not meet the aspirations of the curriculum in relation to the practice of experimental approach, including the inclusion of digital means, which was not effective.
مقال
Keywords: تعليمية الرياضيات ; المسعى العلمي ; البعد التجريبي للرياضيات ; الوسائط الرقمية; mathematics education; scientific approach; the experimental dimension of mathematics; digital means.